Elevated temperature enhances task performance by improving cognitive abilities in common rudd (Scardinius erythrophthalmus) - Monika Sysiak; Ewa Babkiewicz; Marcin Lukasz Zebrowski; Katarzyna Rutkowska; Selvaraj Kunjiappan; Jae-Seong Lee; Piotr Maszczyk (Scientific Reports)
Abstract The thermal sensitivity of task performance in ectothermic organisms may depend on how temperature affects mobility, cognitive ability, or their interaction. Furthermore, these processes may vary with experience or task difficulty. To test these predictions, we performed mesocosm experiments with common rudd (Scardinius erythrophthalmus) foraging for a high-density food reward (Artemia salina nauplii) across consecutive daily sessions under varying task difficulties (short, medium, and long distances to the reward, and presence or absence of experienced individuals) at two temperatures (16–26 °C). Results indicated that the thermal sensitivity of task performance ranged from Q 10  = 2 to 9 across all treatments, peaking during the second and third sessions when fish learned the reward location most intensively. Q 10 values increased with task difficulty, reaching their highest levels when inexperienced fish navigated long distances to the reward and foraged without guidance. In contrast, the thermal sensitivity of mobility remained stable across sessions, with a maximum Q 10 of 2. The significantly higher thermal sensitivity of task performance compared to mobility, along with its positive relationship with task difficulty, suggests that performance improvements at elevated temperatures are driven not only by increased mobility but also by enhanced cognitive processes.